Fluxograma de atendimento de apoplexia hipofisária elaborado a partir do perfil de pacientes atendidos em hospital terciário de Fortaleza entre os anos de 2001 e 2015 - Vasconcelos, Raquel Cavalcante de (2020)
Pituitary apoplexy is a rare disorder that occurs due to a hemorrhage or infarction in the pituitary gland, frequently it occurs in an undiagnosed pituitary tumour. This is a descriptive retrospective study intended to evaluate the profile of patients treated at the Hospital Geral de Fortaleza, in the period between 2001- 2015, with the clinical and radiological diagnosis of pituitary apoplexy and create an attendance flowchart. Forty patients were studied, the average age was 45.9 years with a male predominance (70%), history of smoking and alcohol consumption in 42.4% and in 33.3% of patients, respectively. Among the comorbidities there was the occurrence of hypertension (40%) and diabetes mellitus (20%). The pituitary tumor was evident in 90% of patients, however, only 2.7% of the patients had knowledge of the existence of the tumour. There were reported signs and symptoms of endocrine abnormalities prior to the event, such as amenorrhea in 25% of women, 17.5% of the patients had malaise, nausea and vomiting in 17.5%. Among the signs and symptoms reported during the event, headache predominated (92.5%), followed by visual impairment (60%) and vomiting (47.5%). As regard to hormone dysfunction in the presence of apoplexy, there was predomination ofn the corticotrophic axis (82.5%) followed by gonadotrofic (80%) and the thyrotrofic (77.5%). As for the visual campimetry, the bitemporal hemianopia was present in 72.7% of cases. Among the precipitating factors it was reported aspirin use in 5% of patients. In the image evaluation it was higher the occurrence of pituitary adenoma in 87.5% of cases. The predominant type of tumor was nonfunctioning adenomas (77.7%), and the evaluation of biopsy results showed higher incidence of adenoma (83.3%). The treatment of choice was surgical (80%). No clinical complications were reported after treatment in 77.5% of patients. After treatment, there was the finding of empty sela in 68.5%, improved ophthalmoplegia in 58.6%, and improvement in the visual deficit in 54.2% of patients. There was long term treatment with corticosteroids (85%) and thyroxine (85%). The evaluation of various clinical and endocrine-metabolic characteristics found in these patients, the precipitating factors of pituitary apoplexy, the tumour characteristics, treatment and clinical outcome served as a guide for setting up a treatment protocol forb atients with pituitary apoplexy.